Hubungan Yahudi dengan Orang Samaria: Sejarah, Konflik dan Rekonsiliasi - Simanjuntak, Radius; Simanjuntak, Herbin; Edison (Sekolah Tinggi Teologi Berita Hidup, 2025)
The relationship between Jews and Samaritans is one of the complex historical conflicts, influenced by ethnic, political, theological, and social factors. This tension began since the division of the Kingdom of Israel and was further exacerbated by the policies of foreign kingdoms, such as Assyria and Babylon, which influenced the demographic and religious structure of the region. Jews and Samaritans have significant differences in terms of places of worship and the canon of scriptures, which are the main sources of conflict. This study aims to analyze the dynamics of the relationship between the two groups by reviewing the causes of the conflict and the efforts of reconciliation that have occurred throughout history. This study uses a qualitative approach with a literature study method, referring to academic sources from journals, books, and historical texts such as the notes of Flavius. Josephus and Bible references. The results of the study show that the ethnic and theological separation that occurred since the Babylonian exile period had an impact on social segregation that persisted until the Roman period. However, the teachings of Jesus Christ in the New Testament paved the way for reconciliation by emphasizing the values of inclusivity and love. This study highlights the importance of historical and theological approaches in understanding the dynamics of Jewish-Samaritan relations and their impact on interfaith dialogue in the modern era.